Videos as A Media in Teaching Listening In English Education Study Program IAIN Raden Intan Lampung - Indrasari, Nunun (Lentera: Jurnal Ilmiah Kependidikan, 2016)
One of the important things should be considered in teaching listening is the media used by the teacher. Media can assist the students in learning language. As a facilitator who should give the students chance to learn, a teacher is demanded to choose the suitable media for teaching. This paper attempts to discuss the benefits and how video used as a media in teaching listening. It also aimed to investigate the weaknesses of using video in listening class. Video brings certain information about certain topics. It helps the students in building the knowledge of certain field easier and stimulates the listening comprehension as well since it presents audio and moving image. Video can become an alternative in teaching listening. However, teacher should consider some factors when choosing the video for teaching listening, such as the level of difficulties, the relevant topics, and some aspects related to listening skill like pronunciation of the speaker on the video and clear audio.